An Empirical Analysis of Food Security and Poverty Status Among Rural Farming Households in Owo Local Government Area, Ondo State, Nigeria - Ojo, Olutope Stephen (PT. Riset Press International, 2025)
The study was conducted in the Owo Local Government Area of Ondo State, Nigeria, to analyze food security and poverty among rural farming households. A total of 120 households from six communities were selected using a multistage sampling technique. Primary data was collected through a structured questionnaire. Descriptive statistics, expenditure approach, and multiple regression analysis were used for data analysis. The study found that the average age of farmers was 37.8 years, indicating a young and potentially productive population. Approximately 70% of the rural farming households were male. The average household size was 7, and the average farm size was 1.28 hectares. The households had an average income of N230,005 and a food security index of 1.5, suggesting they were food secure. However, the households were moderately poor. Multiple regression analysis revealed that the gender of the household head, household size, income, and years of education were significant factors in explaining variations in food security, accounting for 70% of the variation. Correlation analysis indicated a significant negative relationship (-0.866) between food security and poverty status, implying that an increase in poverty would decrease food security. Based on these findings, it is recommended that rural households prioritize food production and other productive activities. Promoting formal education among rural households and providing credit facilities to encourage agricultural production would also enhance food security